Data supporting 'Numerical Investigation of full helicopter with and without the ground effect' - Silva, Paulo; Tsoutsanis, Panagiotis (Cranfield University, 2022)
In the present work, the aerodynamic performance of the full helicopter PSP in hover flight is investigated using a simplified concept of multiple reference frame (MRF) technique in the context of high-order Monotone Upstream Centred Scheme for Conservation Laws (MUSCL) cell-centred finite volume method. The predictions were obtained for two ground distances and several collective pitch angle at tip Mach number of 0.585. The calculations were made for both out-of-ground-effect (OGE) and in-ground-effect (IGE) cases and compared with experimental data in terms of pressure distribution and integrated thrust and torque and vortex system.
Keywords: Full helicopter; CFD; PSP; Ground Effect; Pressure distribution